Characterization of skin tumors in an Egyptian large tertiary center: A cross-section study - El-Khalawany, Mohamed; Moheb, Mohammad; Mansour, Mofreh; Ahmed, Omar AbdelHady Omar; Mohamed, Sameh Fahmy; Aladl, Ahmad Saeed; Amer, Mohamed; El Rewiny, Emad; Sallam, Manar Elsayed; Mohammed, Salma S; Shawky, Ahmed (International journal of health sciences, 2024)
Skin tumors are a global health problem caused by UV exposure with ethnic and geographical distribution. This research summarized Egyptian skin tumor features. A cross-sectional study was conducted in the Al-Hussein Teaching Hospital, Al-Azhar University, Cairo, Egypt. Patients’ data were collected from the hospital-recorded registry from January 2010 to December 2020. Results: The age group, 19-59y, showed the highest prevalence, 57% (n=940), of skin tumors. The total number of skin tumor patients was 1649 (males 52.9% (n=872), females 47.1% (n=777). For benign skin tumors, the male-to-female ratio was 1: 0.96, and for malignant skin tumors, the male-to-female ratio was 1: 1.47. The frequency of skin tumors at the sun-exposed site (out of the total n= 1770) was 39.4% (n= 697) and the face showed the highest frequency 25.8% (n=457). The frequency of skin tumors at the non-sun-exposed sites was 60.6% (n=1073) of the total skin tumor number. Basal cell carcinoma (BCC) showed a frequency of 90.1% of cases affecting sun-exposed sites. Therefore, skin tumors have unique characteristics in Egypt, with malignant skin tumors being rare showing more predilection in males. Further studies are needed to emphasize the national characteristics of skin tumors in Egypt.